Retail Design: Color-Light Influence on Brand Identity-Image Perception - Kutlu, Rana; Manav, Banu; Kılanç, Ruken (My University, 2013)
In this study, it is aimed to find out the brand identity in interior design, especially the effects of color and lighting scheme at brand image, retail, store. This paper presents an experimental study by 121 participants with a special emphasis on the influence of color and light on environmental perception in retail design. The perceived image and identity of a store are affected strongly by color and light, for this reason a survey is conducted to measure the perception of the color preferences and lighting scheme in the space in regard to the cognitive memory of customers and store satisfaction by using square method. Regression analysis is applied to identify the role of color and lighting attributes in shopping for the store satisfaction.
Keywords: Retail design; Color; Light; Brand identity; Image perception; Square method